Human rights diplomacy - Mullerson, R. A. (New York : Routledge, 1997)
In this insightful analysis of human rights diplomacy, Rein Mullerson examines the ways in which foreign policy instruments are used to promote human rights abroad, and how human rights issues are used for the sake of other foreign policy aims. The book explores the relationship between human rights and international stability and the role of non-governmental organizations, the business community and mass media in formulating human rights agendas for governments and inter-governmental organizations. Also addressed are issues such as the universality of human rights in a multi-cultural world and the impact of religious and nationalistic extremism. Rein Mullerson concludes by looking at the role of the UN and other international bodies engaged in the promotion of human rights, and how military force can be an option in settling violations.
The author argues that it tends to be regimes that are hostile to human rights that in turn cause instability in the international community. Throughout the book it is demonstrated that a concern for human rights is legitimate because of the impact human rights have on international relations, and because of the common bonds that link all people.
1. The raison d'etre of human rights diplomacy -- 2. Human rights and international stability -- 3. The role of cultural factors, societal development and power interests in the human rights discourse -- 4. Some lessons of Cold War human rights diplomacy -- 5. A new era: what should, and what can, be done? -- 6. Human rights, peace and the use of force.
Includes bibliographical references and index.
Keywords: Human rights; Diplomacy; International relations